Amylose Content of Rice and Quality of Fermented Cake - Perdon, A.A.; Juliano, Bienvenido O. (Wiley, 1975)
The use of aged milled rice with an intermediate amylose content (20–25%) in the preparation of fermented rice cake yielded a steamed cake with a greater volume and an optimum softness as compared with similar cakes prepared from rice with a lower or higher amylose content. Aging of the rice decreased gas (CO2) retention during fermentation, but improved gas retention and cake volume during steaming.